Comparative study of endoscopic band ligation versus injection sclerotherapy with 50% dextrose in water, in symptomatic internal haemorrhoids - Abiodun, Adekunle; Alatise, Olusegun; Okereke, Chukwuma; Adesunkanmi, Abudul-Rashid; Eletta, Emmanuel; Gomna, Alexander (The Nigerian postgraduate medical journal, 2020)
Background: Haemorrhoids are common anorectal conditions seen in surgical practice, with various treatment modalities. This study compared the short-term outcome of injection sclerotherapy with 50% dextrose in water and rubber band ligation in the management of second-and third-degree haemorrhoids, in terms of symptoms improvement, complications, recurrence rate, retreatment rate and acceptability. Methodology: This was a prospective comparative study that was carried out in the endoscopic unit of the Obafemi Awolowo University Teaching Hospitals Complex, Ile-Ife, in southwestern Nigeria. Sixty consecutive patients with second- and third-degree haemorrhoids, who consented, were recruited into the study and were randomised into two groups. Group A had endoscopic injection sclerotherapy and Group B had endoscopic rubber band ligation. Results: With regard to anal protrusion, more patients consistently reported either complete (16 [64.4%]) or partial (9 [40.9%]) resolution of symptoms in Group B, compared to Group A which had 7 (28.0%) and 5 (22.7%) cases, respectively (P = 0.03). Resolution of anal bleeding was initially more in Group B than A (22 [95.7%] vs. 17 [77.3%] patients, respectively), in the first 24-h post-treatment; however, within the 1st week, this ratio was reversed (P = 0.07). The retreatment rate for Group A and B was 23.3% and 13.3%, respectively,P = 0.34. More patients in Group B experienced severe pain post-treatment compared to Group A (P = 0.01). Three-month post-treatment, two (11.8%) patients in Group A and one (4.5%) in Group B had recurrence of anal bleeding (P = 0.42). There was no recurrence in anal protrusion in both treatment groups. Conclusion: Endoscopic rubber band ligation had a significantly higher success rate than endoscopic injection sclerotherapy, in terms of resolution of anal protrusion, but with higher pain score.